2017
DOI: 10.1080/02791072.2017.1290304
|View full text |Cite
|
Sign up to set email alerts
|

The Blue Lotus Flower (Nymphea caerulea) Resin Used in a New Type of Electronic Cigarette, the Re-Buildable Dripping Atomizer

Abstract: The blue lotus flower (Nymphea caerulea) is an Egyptian water lily containing apomorphine and nuciferine. Apomorphine has been described as a psychoactive alkaloid and is a non-selective dopamine agonist primarily used to treat Parkinson’s disease as it stimulates dopamine receptors and improves motor function. Nuciferine is an alkaloid associated with dopamine receptor blockade. Today, blue lotus flower is used as a sleep aid and anxiety reliever. The rebuildable dripping atomizer (RDA) is an electronic cigar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Users have reported that dripping creates larger clouds, enhances flavor, and gives stronger throat hits than other EC models [44]. Dripping devices have also been used with illicit drugs [45]. Some RDAs have tanks (referred to as RDTAs) that automate the dripping process, which helps prevent dry puffing and eliminates the need to frequently drip e-liquid onto the coils [22].…”
Section: Discussionmentioning
confidence: 99%
“…Users have reported that dripping creates larger clouds, enhances flavor, and gives stronger throat hits than other EC models [44]. Dripping devices have also been used with illicit drugs [45]. Some RDAs have tanks (referred to as RDTAs) that automate the dripping process, which helps prevent dry puffing and eliminates the need to frequently drip e-liquid onto the coils [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nymphea carulea (Blue Lotus): 2017 analysis of apomorphine and nuciferine in a confiscated brown resin material [ 796 ];…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…The blue lotus flower has two main alkaloids exhibiting its pharmacological effects: apomorphine and nuciferine. Apomorphine has been used to treat ailments, diseases, and disorders such as insomnia, depression, Alzheimer's disease, and schizophrenia 6 . Acting as a nonselective dopamine receptor agonist and activating serotonin and α‐adrenergic receptor, apomorphine has also been used in the treatment of alcohol and morphine addiction 6 .…”
Section: Overview Of Natural Productsmentioning
confidence: 99%